Reproduction performance of female Nile tilapia under different environments and age classes - Yoshida, Grazyella Massako [UNESP]; Oliveira, Carlos Antonio Lopes De; Kunita, Natalí Miwa; Rizzato, Gabriel Soriani; Ribeiro, Ricardo Pereira (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
Current assay verifies the reproductive performance of females of Nile tilapia in different age classes and reproductive environments. Four hundred and fifty-one females were evaluated in two different Brazilian environments, namely in Maringá, Paraná State, Brazil (Site 1 - hapas of 10 m3 and Site 2 - hapas of 1 m3) and in one environment in Alfenas, Minas Gerais State, Brazil (Site 3 - hapas of 14 and 28 m3). The females were divided into three age classes, corresponding to animals under one year (age 1); between one to two years (age 2); and over three years old (age 3). Spawning was verified once a week, from October 2012 to March 2013, corresponding to a 23-week assessment. The statistical analyses were performed with Proc Genmod from the statistical program SAS. Site 2 had the lowest results when compared to the other sites for multiple spawning, spawning frequency and volume of eggs/female for animals of age 2. Statistical differences were not detected between ages 1 and 2 for the same assessment site, although females at age 3 in Site 3 provided higher results than those at age 2. Results show that, precluding the use of animals in individual hapas (1 m³) and maintaining older females in the stock, may improve reproduction results.

Objetivou-se verificar a performance reprodutivas de fêmeas de tilápia do Nilo em diferentes classes de idade e ambientes reprodutivos. O conjunto de dados foi composto por 451 fêmeas avaliadas em dois ambientes na cidade de Maringá, Estado do Paraná (hapas de 10 m3 - Local 1 e hapas de 1 m3 - Local 2) e em um ambiente em Alfenas, Estado de Minas Gerais (Local 3 - hapas de 14 e 28 m³). As fêmeas foram divididas em três classes de idade, correspondendo a animais de até um (Idade 1), entre um e dois (Idade 2) e com mais de três anos (Idade 3). A verificação de desovas foi realizada uma vez por semana no período de outubro/2012 a março/2013, correspondendo a 23 semanas de avaliação. Realizaram as análises estatísticas utilizando o procedimento Proc Genmod do programa estatístico SAS. O Local 2 apresentou resultados inferiores aos demais locais para todas as características estudadas ao utilizar animais de Idade 2. Diferenças estatísticas não foram observadas entre Idade 1 e 2 para o mesmo local de avaliação, no entanto a Idade 3 presente no Local 3 apresentou resultados superiores ao comparar com fêmeas de Idade 2. Desta forma, evitar o uso de animais em hapas individuais (1 m³) e manter fêmeas mais velhas no plantel podem melhor os resultados reprodutivos.
Performance reprodutiva de fêmeas de tilápias do Nilo em diferentes ambientes e classes de idade
Keywords: Oreochromis niloticus; spawning; volume of eggs.; Oreochromis niloticus; desova; volume de ovos.